Moderate physical activity from childhood contributes to metabolic health and reduces hepatic fat accumulation in adult rats - De Moura, Leandro Pereira [UNESP]; Da Silva Sponton, Amanda Christine [UNESP]; De Araújo, Michel Barbosa [UNESP]; Dalia, Rodrigo Augusto [UNESP]; Pauli, José Rodrigo [UNESP]; De Mello, Maria Alice Rostom [UNESP] (Springer Nature, 2013)
Background: Obesity, oxidative stress and inflammation, by triggering insulin resistance, may contribute to the accumulation of hepatic fat, and this accumulation by lipotoxicity can lead the organ to fail. Because obesity is growing at an alarming rate and, worryingly, in a precocious way, the present study aimed to investigate the effects of moderate physical training performed from childhood to adulthood on liver fat metabolism in rats. Methods. Twenty rats that were 28days old were divided into two groups: control (C) and trained (T). The C Group was kept in cages without exercise, and the T group was submitted to swimming exercise for 1hour/day, 5days/week from 28 to 90days of age (8weeks) at 80% of the anaerobic threshold determined by the lactate minimum test. At the end of the experiment, the body weight gain, insulin sensitivity (glucose disappearance rate during the insulin tolerance test), concentrations of free fatty acids (FFA) and triglycerides (TG) and hepatic lipogenic rate were analyzed. For the statistical analysis, the Student t-test was used with the level of significance preset at 5%. Results: The T group showed lower body weight gain, FFA concentrations, fat accumulation, hepatic lipogenic rate and insulin resistance. Conclusion: The regular practice of moderate physical exercise from childhood can contribute to the reduction of obesity and insulin resistance and help prevent the development of accumulation of hepatic fat in adulthood. © 2013de Moura et al; licensee BioMed Central Ltd.
Keywords: Hepatic fat accumulation; Metabolic health; Moderate exercise; fatty acid; lactic acid; triacylglycerol; animal experiment; animal tissue; controlled study; insulin resistance; insulin sensitivity; insulin tolerance test; lipid metabolism; lipid storage; lipolysis; liver metabolism; nonhuman; obesity; physical activity; rat; swimming; weight gain; Adipose Tissue; Age Factors; Animals; Animals, Newborn; Blood Glucose; Body Weight; Fatty Acids; Insulin; Insulin Resistance; Lactic Acid; Lipogenesis; Liver; Physical Conditioning, Animal; Rats; Rats, Wistar; Swimming; Triglycerides; Rattus